-1 1/7k•(-1 3/4p)•(-1/2m)= -kpm
1) -1 1/7k•(-1 3/4p)=(8/7•7/4)kp=2kp
2)2kp•(-1/2m)= -(2•1/2)kpm= -kpm
Ответ: -kpm
Пошаговое объяснение:
-1 1/7к * (-1 3/4р) * (-1/2m) =
(-1 1/7 * (-1 3/4) * (-1/2)) * k * p * m =
(-8/7 * (-7/4) * (-1/2)) * k * p * m =
(-2/1 * (-1/1) * (-1/2)) * k * p * m =
(2/1 * (-1/2)) * k * p * m =
-2/2 * k * p * m = -1 * kmp = -kmp
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
-1 1/7k•(-1 3/4p)•(-1/2m)= -kpm
1) -1 1/7k•(-1 3/4p)=(8/7•7/4)kp=2kp
2)2kp•(-1/2m)= -(2•1/2)kpm= -kpm
Ответ: -kpm
Пошаговое объяснение:
-1 1/7к * (-1 3/4р) * (-1/2m) =
(-1 1/7 * (-1 3/4) * (-1/2)) * k * p * m =
(-8/7 * (-7/4) * (-1/2)) * k * p * m =
(-2/1 * (-1/1) * (-1/2)) * k * p * m =
(2/1 * (-1/2)) * k * p * m =
-2/2 * k * p * m = -1 * kmp = -kmp